Relationship of Neutrophil Lymphocyte Ratio and Glomerulus Filtration Rate in Diabetic Nephropathy Patients at H. Adam Malik Hospital, Medan, Indonesia - Merlin, Asri; Siregar, Jelita; Syafril, Santi (Indonesian Journal of Medicine, 2024)
Background: Diabetic nephropathy is a serious complication of diabetes mellitus (DM). The neutrophil-lymphocyte ratio is the result of the relative count of neutrophils divided by the relative number of lymphocytes in diabetic nephropathy patients in % units obtained from routine hematology results using EDTA blood samples and measured by flow cytometry with Sysmex XN-1000, glomerular filtration rate was measured according to the Cockroft-Gault formula. This study aimed to determine the relationship between neutrophil lymphocyte ratio (NLR) and glomerular filtration rate in diabetic nephropathy patients. Subjects and Method:  This was a cross sectional study conducted at H. Adam Malik Hospital, Medan, North Sumatera, Indonesia, from November 2022 – January 2023. 30 diabetic nephropathy patients were selected for this study consecutively. The dependent variable was the glomerular filtration rate. The independent variable was the NLR. Blood sample was taken for a complete blood count and creatinine examination. Data were analyzed using the Spearman test. Results: NLR was negatively associated with eGFR in patients with diabetic nephropathy, but it was statistically non significant (r= -0.25; p= 0.186). Conclusion: NLR is negatively associated with eGFR in patients with diabetic nephropathy, but it is statistically non significant.  Keywords: neutrophil lymphocyte ratio, glomerular filtration rate, diabetic nephropathy